RELEVANSI EVALUASI PENGELOLAAN DAERAH IRIGASI TALAWAAN MERAS PROVINSI SULAWESI UTARA - Friska Anastasya Saki; Leo Kalesaran; David P. Rumambi (COCOS, 2023)
AbstractThe objectives of this research were:: 1) to obtain information about evaluationin the Talawaan Meras Irrigation Area, 2) To evaluate the Management of IrrigationNetworks in the Talawaan Meras Irrigation Area. This research was carried outdirectly in the field and data collection was carried out using survey methods andinterviews with several selected respondents, as well as measurement/calculation ofthe characteristics of variables related to irrigation networks carried out directly onthe research object. The conclusions from this study are (1) The research location ofMS.3.Kr, which was originally 20 ha for rice fields, now the designation is no longerrice fields, but inland fisheries. (2) Measurement of water discharge in the secondarychannel at the MS.3.Kr location uses the float method, and the average dischargeobtained is 0.16 m^3/second. (3) The existing irrigation structures in the TalawaanMeras Irrigation Area are all in good condition and can function properly. (4) Theplanting season determined by the Agriculture Service is not in accordance with thefacts on the ground. (5) In the last 2 years, performance evaluation in the TalawaanMeras Irrigation Area on MS.3.Kr has not been carried out properly due to a lack ofoperational funds. Funds that should have been there have been focused on Covid-19funds. (6) There are 9 irrigation network officers in Talawaan Meras, but not all ofthem are active. At the MS.3.Kiri location, there is only one irrigation network officerwho has taken over all the tasks at that location.Keywords : evaluation, irrigation area management, Talawaan Meras